The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1088/0022-3727/41/5/055401
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of defect point to improve response time via controlled azimuthal anchoring in a vertically aligned liquid crystal cell with polymer wall

Abstract: Conventional multi-domain vertically aligned liquid crystal (LC) cells have defect points due to the collision of LC directors during the formation of multiple domains. In addition, the location of defects changes with time resulting in a slow response time. This paper proposes a robust vertically aligned LC cell, where the LCs are locked by polymer walls, and the azimuthal anchoring on the surface of the alignment layer is controlled by the polymerization of a UV curable reactive mesogen monomer. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…They claimed that the proposed device exhibits a higher transmittance, better dark state, and faster response time as compared to the MVA device. In 2007 and 2008, our group [23][24][25][26] reported the surface polymer stabilization of the LC director in a PVA device and other VA devices using a reactive mesogen (RM), showing a considerable improvement in the rise time, in which the doping amount of the RM was about 0.1 wt.% in the LC host. Recently, Hsu et al 27 reported detailed results on the optical performance of a polymer-stabilized mobile MVA-LCD according to the curing process of the reactive monomer with a doping amount of 0.05 wt.%.…”
Section: History Of Related Technologymentioning
confidence: 99%
“…They claimed that the proposed device exhibits a higher transmittance, better dark state, and faster response time as compared to the MVA device. In 2007 and 2008, our group [23][24][25][26] reported the surface polymer stabilization of the LC director in a PVA device and other VA devices using a reactive mesogen (RM), showing a considerable improvement in the rise time, in which the doping amount of the RM was about 0.1 wt.% in the LC host. Recently, Hsu et al 27 reported detailed results on the optical performance of a polymer-stabilized mobile MVA-LCD according to the curing process of the reactive monomer with a doping amount of 0.05 wt.%.…”
Section: History Of Related Technologymentioning
confidence: 99%
“…The conventional multi-domain VA (MVA) [2][3][4][5][6] and patterned VA (PVA) [7][8][9] have shortcomings, such as low transmittance and slow rise response time. In order to overcome the slow rise response time of such VA modes, the polymer-stabilized VA (PS-VA) mode [16][17][18][19][20] has recently been proposed, but the low-transmittance issue still persists and furthermore gives rise to a power consumption issue when employed in high resolution LCDs such as ultra-high-definition (UHD) LCDs. In a PS-VA device as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] For instance, Kim et al [14] proposed a robust vertically aligned LC cell, where the LC were locked by polymer walls, and the azimuthal anchoring on the surface of the alignment layer was controlled by the polymerisation of a UV curable reactive mesogen monomer. As a result, the defect points were trapped at a single position, resulting in a greatly improved response time.…”
Section: Introductionmentioning
confidence: 99%